Metodologia para obtenção de dados e informações em logística urbana: estudo de caso da região metropolitana de Belo Horizonte - Charliston Marques Moreira (2012)
The metropolitan areas are experiencing a time of worsening mobility problems. One reason is the lack of integrated planning of all activities that interfere with their performance. Historically, this lack of integration is present in the marginal treatment given to carry loads. Currently the negative consequences of this treated triggering a growing effort to solve their problems. This effort is also present in the guidelines given by the government, which recently enacted Law 12,587 in order to integrate the different modes of transport and improve accessibility and mobility of people and cargo in the territory of the municipalities. Both the definition of guidelines such as the transportation planning activities requires a solid database to support decision making. This paper tries to act exactly this point by proposing a methodology for gathering data and information on urban logistics. The proposed methodology was applied in a pilot survey in the BHMA. The stages of development included: literature review, discussions with stakeholders, creating questionnaires, defining the methodology of data collection, implementation of the pilot survey and data analysis.